Molecular evidence for association of Papaya ringspot virus with papaya from North East Hill region of India - SUSHEEL KUMAR SHARMA, PINKI PAL; S.V. NGACHAN, HEMAVATI RANEBENNUR* (Indian Phytopathology, 2017)
Papaya ringspot virus (PRSV) is a major bottleneck in papaya production globally. The incidence of PRSV was as high as 51% in West Tripura district of Tripura followed by Imphal West of Manipur (41.6%) exhibiting the typical symptoms of yellowing, vein clearing, mottling, severe blistering with distorted leaves and concentric rings on the fruits. The papaya cultivars RCTP 1, Red Lady and Manipur local exhibited typical symptoms of PRSV under sap inoculation. The typical flexuous particles of size 800 X 12 nm were observed in the electron microscope. The amplicons of size 350 bp were observed in RT-PCR using the primers derived from the conserved NIb region of Potyvirus genome. Two PRSV isolates from North East India (PRSV-Mnp1 and PRSV-Trp1) had maximum identity of 83.1 to 84 % with PRSV isolates from Thailand, Taiwan and Korea for conserved NIb genomic region. Phylogenetically PRSV isolates from North East India segregated to a distinct cluster compared to other isolates from different papaya growing regions of the world. It is the first molecular evidence for the association of PRSV with papaya from North-East region of India.